Auditoría Macroproceso Docencia, desarrollo agenda académica profesoral de la Universidad del Quindío, Facultades de Ingeniería y Ciencias Agroindustriales. (2012)
The Operative Macro-Process Audit of Teaching Development of Professorial Academic Agenda Code: M.DO-02.0107 of the University of Quindío in the Colleges of Agro-Industrial Sciences and Engineering, was conducted by using techniques and procedures necessary to conduct this audit. This audit was based on the general knowledge of each of the colleges mentioned, was continued with the analysis and verification of information provided by each department and each program, by the Office of the University